Designing Game-Based Service Desk towards User Engagement Improvement - Kridanto Surendro; Sarifah Putri Raflesia (Institute of Advanced Engineering and Science, 2016)
Along the implementation of Information Technology (IT), there are incident, request, problem, and event. According to this, organizations need to implement a function which can be a single point to provide communication between IT service provider and IT users. Information Technology Infrastructure Library (ITIL) mentions service desk as a function to operate solution of this matter. But, recently organizations find new challenge which is related to service desk staffs’ motivation. The repeated activities which are run by service desk may cause saturation. This situation will affect workplace enviroment and productivity. In this research, we propose a design to help organization build game-like activities as solution to boost service desk’s motivation which can give good impact to service desk’s quality. Our proposed design uses game approach and ITIL practices to ensure that game-based service desk is well designed.